Binary supramolecular networks of bridged triphenylamines with different substituents and identical scaffolds. Issue 82 (1st October 2018) - Steiner, Christian; Yang, Zechao; Gliemann, Bettina D.; Meinhardt, Ute; Gurrath, Martin; Ammon, Maximilian; Meyer, Bernd; Kivala, Milan; Maier, Sabine
Abstract : Based on scanning tunneling microscopy experiments combined with density functional theory, we report the formation and the electronic structure of porous binary supramolecular networks on Au(111). Abstract : Based on scanning tunneling microscopy experiments combined with density functional theory, we report the formation and the electronic structure of porous binary supramolecular networks on Au(111). The two triphenylamine derivatives with identical scaffolds intermix due to a maximization of the overall number of H-bonds instead of an optimization of the H-bond strength in the bonding motif. The HOMO–LUMO gap is defined by both molecules, which is typical for electron donor–acceptor networks.